Case study for the 10th grade section A, at the unidad educativa bilingüe Americano, school year 2021-2022 - Chalen Tigrero, Yajaira Julissa (2023)
In this case study, one of the problems is the student’s attention deficit which brings with it the loss of concentration by thoughts, irrelevant sounds or antipathy for the English subject that does not allow activities during class time. Furthermore, low cognitive ability by factors such as distraction or learning problems are often more perceptible negative features when learning a second language. The methodology applied for this case study was observation, that is, observing and analyzing the behavior of the students to diagnose a problem during the learning of a new language. This case study was developed based on the observation of the 10th grade Section A, which is composed of 40 students, who are between 14 and 15 years old, from the “Americano High School”, working with the grammar point “Simple Present focusing on Daily Routines” The application of new strategies such as flashcards that often attracts students' attention while learning a new English. This document shows the analysis of the case study, as well as the evidence of the demonstration class before the 10 th grade students